The Effect of Cooperative Learning Model Type Two Stay Two Stray and Learning Style on Social Sciences Learning Outcomes of Grade IV Elementary School Students - Irfanto, Wachid Yuli; Mustaji, Mustaji; Jacky, Muhammad (Universitas Malikussaleh, 2019)
This study aims to determine the existence of significant differences in students who carry out learning using the two stay two stray model and learning styles towards learning outcomes. The design used in this study is the Pre-Experimental Design design of the One-Group Pretest-Posttest Design. The technique of data analysis using validity and reliability tests. The average results of the pretest and posttest values obtained in the research subjects (class IV) showed that there was an increase before the treatment and after treatment, both students who had the type of visual learning style, audiovisual and kinesthetic. In the type of visual learning style, the pretest score was 65.24 while the posttest score was 79.17. For the type of audio-visual learning style, the pretest score was 66.74, while the posttest score was 82.26 and for the last type, the kinesthetic learning style obtained a pretest score of 67.32 while the posttest score was 84.75. All types of student learning styles experience increased learning outcomes when given treatment with model two stay two strays. So from that shows that the learning model of two stay two stray with visual learning style, audiovisual and kinesthetic experiences a significant increase in improving student learning outcomes.